The Adverse Childhood Experiences of Methamphetamine Users in Aotearoa/New Zealand - Bax, Trent (International Journal of Criminology and Sociology, 2021)
Using in-depth semi-structured interviews, the family environment of forty-one former frequent methamphetamine users is analyzed using a ten category measure of adverse childhood experiences (ACEs). The qualitative analysis reveals almost three-quarters experienced four or more ACEs, especially parental separation, parental substance abuse, emotional neglect and physical neglect. Females compared to males, and Māori compared to European/Pākehā, experienced more adversity, while father figures played a disproportionate role in producing participants’ childhood adversity. Physical neglect, physical abuse, parental mental illness, sexual abuse and early age of parental separation were especially detrimental to participants’ healthy development. With approximately five ACEs each on average, this first ever life course-based qualitative study of frequent methamphetamine users in Aotearoa/New Zealand adds further evidence to the body of knowledge that demonstrates frequent substance use is an adaptive counterproductive coping mechanism to adverse childhood experiences. However, six interviewees were exposed to none or one ACE. With ‘good’ and ‘fortunate’ childhoods, and loving and supportive parents, such contrary childhoods underscore the importance of cultivating and practicing prosocial authoritative parenting practices.